Early general movements and brain magnetic resonance imaging at term-equivalent age in infants born < 30 weeks' gestation. (October 2016) - Olsen, Joy E.; Brown, Nisha C.; Eeles, Abbey L.; Einspieler, Christa; Lee, Katherine J.; Thompson, Deanne K.; Anderson, Peter J.; Cheong, Jeanie L.Y.; Doyle, Lex W.; Spittle, Alicia J.
Abstract: Background: Neurodevelopmental assessments and brain magnetic resonance imaging (MRI) at term-equivalent age (TEA) predict developmental outcomes in preterm infants. However, the relationship between neurodevelopment prior to term and cerebral structure is currently unknown. Aims: To examine the relationships between General Movements (GMs) assessed from birth to TEA and brain MRI at TEA in infants born < 30 weeks' gestation. Study design: Prospective cohort study. GMs (categorised as 'normal' or 'abnormal') were recorded weekly from birth to 32 weeks, and at 34 and 36 weeks' postmenstrual age. At TEA, GMs were assessed concurrently with brain MRI (using a validated scoring system). Subjects: 149 infants born < 30 weeks' gestation were recruited from a tertiary hospital. Results: 103 infants had MRI at TEA and GMs recorded. Abnormal GMs prior to term were associated with cortical grey matter abnormality ( p  < 0.03), deep grey matter abnormality ( p  = 0.02) and increased interhemispheric distance ( p  < 0.02). Abnormal GMs at TEA ( n  = 55/90) were associated with more global brain abnormality ( p  < 0.01) and cortical grey matter abnormality ( p  = 0.01), and decreased transcerebellar diameter ( p  = 0.04) on concurrent brain MRI. Conclusions: Abnormal GMs both prior to term and at TEA were associated with more marked brain abnormality, and smaller brains at TEA. Abnormal GMs are an early marker of brain abnormalities in very preterm infants. Highlights: Abnormal general movements (GMs) prior to term are an early marker of brain abnormality Abnormal GMs are associated with disrupted brain development as well as injury in very preterm infants Abnormal GMs are associated with more marked brain abnormality and smaller brains on MRI at term-equivalent age Early GM assessment can identify very preterm infants at risk for adverse neurodevelopment